Human sickness behavior: Ultimate and proximate explanations. Issue 1 (13th January 2015) - Shattuck, Eric C.; Muehlenbein, Michael P.
ABSTRACT Sickness behavior, a coordinated set of behavioral changes in response to infection, lies at the intersection of immunology, endocrinology, and evolutionary biology. Sickness behavior is elicited by pro‐inflammatory cytokines, is thought to be an adaptive means of redirecting energy away from disadvantageous behaviors and toward mounting an effective immune response, and may be modulated by hormones, including testosterone and oxytocin. Research on sickness behavior in humans has lagged behind non‐human animal research due to methodological complexities. Here we review what is known about sickness behavior in humans, the effects of various hormones on sickness behavior, the possible role of cytokine gene variation in influencing sickness behavior responses, and the ways in which culture and gender norms could similarly influence these behavioral changes. We also propose methodologies for advancing further studies of sickness behavior in humans. Am J Phys Anthropol 157:1–18, 2015. © 2015 Wiley Periodicals, Inc.